Rekonstruksi Kompetensi Kepribadian Guru Berbasis Makarim Al-Syari’ah sebagai Fondasi Penguatan Profesionalisme Guru Madrasah - Isnadia, Ririn; Anisa, Dian Rofi; Ardini, Fhina; Mufidah, Hana; Hawa, Sitti; Wahyuni, Sri (Jurnal Pendidikan Madrasah, 2026)
The era of disruption and digitalization presents increasingly complex challenges for the educational sector, requiring teachers not only to possess strong academic and pedagogical competencies but also to demonstrate resilient personal character in responding to moral crises and the evolving characteristics of students. This study aims to reconstruct teachers’ personality competence through the integration of Makārim al-Syarī‘ah values as a foundational framework for strengthening teacher professionalism in madrasah education. Employing a qualitative approach with a library research method, the study analyzes a range of scholarly literature related to teacher personality competence, the concept of Makārim al-Syarī‘ah, and professional standards for educators. The findings reveal that the reconstruction of personality competence based on Makārim al-Syarī‘ah, which emphasizes the purification and development of the human soul through the values of hikmah (wisdom), ‘iffah (self-restraint), syajā‘ah (moral courage), and ‘adālah (justice), is capable of transforming teachers into authentic role models (uswah hasanah) with strong integrity and exemplary character. The integration of these virtues contributes to the enhancement of professional ethics, spiritual responsibility, honesty, and moral commitment in educational practice. This study concludes that personality competence grounded in religious values constitutes a strategic factor in improving the quality of madrasah education, as it directly influences students’ character development, learning motivation, and the creation of a conducive and adaptive educational environment in the digital age.